Faktor Penghambat Penerapan Peraturan Daerah Nomor 1 Tahun 2018 Tentang Ketertiban Umum di Kota Gorontalo - Haikal Pontoh; Lisnawaty W. Badu; Nuvazria Achir (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the factors hindering the implementation of Regional Regulation Number 1 of 2018 concerning Public Order in Gorontalo City. The method used is empirical legal research with a descriptive analytical approach, through the collection of primary data in the form of interviews and observations, as well as secondary data from laws and regulations and related literature. The results indicate that the implementation of this regional regulation has not been effective, as indicated by the continued occurrence of various violations in public spaces. The main inhibiting factors include low public legal awareness, weak law enforcement by officials, the community's economic conditions, lack of regulation dissemination, and limited facilities and infrastructure. Therefore, comprehensive and sustainable efforts are needed to improve the effectiveness of regional regulation implementation by strengthening law enforcement, increasing public awareness, and policies that are more responsive to the community's socio-economic conditions.